The Philosophy of Islamic Finance and its Implications for Islamic Accounting - Salwa, Siti; Atmo Prawiro, Atmo Prawiro; Sugeng Priyono, Sugeng Priyono (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
The philosophy of Islamic finance is rooted in Islamic principles, upholding justice, transparency, and social responsibility as the foundations of the economy. Unlike conventional finance, which is oriented toward profit maximization, this philosophy prohibits usury, uncertainty, and gambling, and encourages investment in the real sector and profit-sharing practices to achieve comprehensive welfare (falah). These philosophical implications are highly significant for the concept of Islamic accounting. Islamic accounting not only aims to present relevant financial information but also ensures compliance with Islamic principles and reports on social performance. This is reflected in the recognition of income and expenses derived solely from halal sources, specific accounting treatment for Islamic contracts, and broader disclosure regarding Sharia Supervisory Board compliance and social contributions such as zakat. Thus, Islamic accounting functions as an accountability tool that reflects the ethical and moral values upheld in Islamic financial philosophy, aiming to achieve a fair and integrity-based economic system.